COMPARISON BETWEEN TRANSRECTAL ULTRASONOGRAPHY GUIDED TRANSRECTAL PROSTATE BIOPSY AND TRANSRECTAL ULTRASONOGRAPHY GUIDED TRANSPERINEAL PROSTATE BIOPSY - Halfian, Randa; Soebadi, Doddy M; Rizaldi, Fikri (Indonesian Urological Association, 2019)
Objective: Prostate cancer is the fourth most common malignancy in men. TRUS guided transperineal prostate biopsy and TRUS guided transrectal prostate biopsy are two main approach to take prostate tissue as diagnostic of prostate cancer. To compare prostate biopsy approach between TRUS guided transrectal and TRUS guided transperineal toward duration of examination, pain perception, and complications. Material & Method: This study was an experimental study with prospective approach. There were two groups, group one was performed TRUS guided transrectal prostate biopsy (TRB) and group two was performed TRUS guided transperineal prostate biopsy (TPB). Evaluation was based on the duration of examination, pain perception, and complication. Data was analyzed using independent T test for duration of examination and Mann-Whitney test for pain perception. Data was performed using SPSS 21.0 version. The statistical significant difference was consider if p value <0.05. Results: There were 20 samples in this study. There was a significant difference in the duration of examination, the average duration of TPB examination (17.40 ± 2.50) was longer than the duration of TRB examination (14.1 ± 2.77). There was no significant statistical difference between TPB group and TRB group in pain perception when USG probe into the anal (p=0.65), anesthesia process (p=0.28), prostate tissue sampling (p=1.00), and post biopsy (p=0.34). Rectal bleeding was found mostly in TRB group (40%) compared to TPB group (0%). Hematuria was experienced by three patients (30%) in TRB group and two patients (20%) in TPB group. Conclusion: TRB was more effective in duration of biopsy than TPB. The complications of rectal bleeding and hematuria were more in TRB group than TPB. The pain perception were the same between both groups. There were no fever, sepsis, hematospermia and vasovagal event in two groups.